1995
DOI: 10.1103/physrevlett.74.387
|View full text |Cite
|
Sign up to set email alerts
|

Simple Maps with Fractal Diffusion Coefficients

Abstract: We consider chains of one-dimensional, piecewise linear, chaotic maps with uniform slope. We study the diffusive behaviour of an initially nonuniform distribution of points as a function of the slope of the map by solving Frobenius-Perron equation. For Markov partition values of the slope, we relate the diffusion coefficient to eigenvalues of the topological transition matrix. The diffusion coefficient obtained shows a fractal structure as a function of the slope of the map. This result may be typical for a wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
157
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(161 citation statements)
references
References 42 publications
4
157
0
Order By: Relevance
“…For simple one-dimensional hyperbolic maps it was shown that the diffusion coefficient is typically a fractal function of control parameters [37,38,39,40]. Subsequently an analogous behavior was detected for other transport coefficients [41,42], and in more complicated models [27,28,29].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…For simple one-dimensional hyperbolic maps it was shown that the diffusion coefficient is typically a fractal function of control parameters [37,38,39,40]. Subsequently an analogous behavior was detected for other transport coefficients [41,42], and in more complicated models [27,28,29].…”
Section: Introductionmentioning
confidence: 83%
“…For all three maps there is a very analogous oscillatory behavior of the parameter-dependent diffusion coefficient. These oscillations can be explained in terms of the changes of the microscopic dynamics under parameter variation, that is, whenever there is a local maximum there is an onset of strong backscattering in the dynamics yielding a local decrease of the diffusion coefficient in the parameter, and vice versa at local minima [37,38,39,40]. However, the five Markov partition series for the climbing sine diffusion coefficient already indicate that there are more irregularities on finer scales.…”
Section: Computing and Comparing The Diffusion Coefficient For Approxmentioning
confidence: 99%
See 2 more Smart Citations
“…[53,54]. Here we will consider the shape of the diffusion coefficient, D, as a function of the slope a for a > 2.…”
Section: Fractal Forms For Diffusion Coefficientsmentioning
confidence: 99%